Phase Transformation, Micro-structure, Crystal Growth Kinetics of Fe3+-Doped Titanium Dioxide Prepared by TiCl4 Hydrolyzation - Shui, Miao; Song, Yue; Wang, Qingchun; Ren, Yuanlong (Asian Journal of Chemistry, 2010)
Titania based ceramics are promising materials for environmental sensors, high efficiency photocatalyst. Ion doping is an effective method to improve the properties by modifying their microstructure and phase composition. In this study, pure TiO2, co-precipitation Fe3+-doped TiO2 and step-precipitation Fe3+-doped TiO2 are synthesized by means of TiCl4 hydrolyzation. Thermal analysis, TEM and X-ray diffraction are used to characterize the Fe3+-doped TiO2 powder. Micro-strain, crystallite size, phase content and cell parameters are calculated according to rietveld refinement software GSAS. The interaction mechanism of Fe3+ in crystal lattice of titanium dioxide and the crystal growth kinetics Fe3+-doped TiO2 are intensively investigated.